Gugatan Actio Pauliana terhadap Pengalihan Utang Komisaris dalam Kepailitan Perseroan Terbatas: (Studi Putusan Mahkamah Agung Nomor 436 K/Pdt.Sus-Pailit/2021) - Mona Lamtiur Es. Cape; Sunarmi; Mahmul Siregar (CV Rewang Rencang, 2025)
Actio Pauliana lawsuit becomes a legal instrument that can be used by curators to cancel debt transfers that harm bankruptcy assets and creditor masses. The method used is normative juridical research method through library studies to obtain secondary data in the form of primary, secondary, and tertiary legal materials related to the problems studied. This research has a descriptive nature, and the data is analyzed qualitatively. Based on the research results, it can be concluded that the transfer of commissioners' personal debts to limited liability companies is generally invalid because it violates the principle of separate legal entity, creates conflict of interest, and potentially harms creditors, so it can be canceled through Actio Pauliana lawsuits if it meets the elements regulated in Law No. 37 of 2004. Supreme Court Decision Number 436 K/Pdt.Sus-Pailit/2021 demonstrates the proper application of Actio Pauliana by prioritizing creditor interest protection and affirming that peace agreements cannot bind curators in carrying out their duties to maximize bankruptcy asset recovery.